Cu Diffusion‐Driven Dynamic Modulation of the Electrical Properties of Amorphous Oxide Semiconductors. (3rd May 2017) - Yeon, Han‐Wool; Jo, Janghyun; Song, Hochul; Kang, Youngho; Na, Sekwon; Yoo, Hyobin; Lee, Seung‐Yong; Cho, Haelim; Kang, Ho‐Young; Jung, Jung‐Kyu; Han, Seungwu; Kim, Miyoung; et al.
Abstract : The exact role of Cu in the electrical properties of amorphous oxide semiconductors (AOSs) has been unclear, even though Cu has been the key element for the p‐type characteristics of crystalline oxide semiconductors. Here, the dynamic changes, determined by diffusion kinetics, in the effect of Cu on the electrical properties of amorphous InGaZnO (a‐IGZO) are revealed. In the early stage of annealing, Cu dominantly diffuses into a‐IGZO through the free volume and acts as a mobile electron donor, which generates a resistive switching (RS) behavior related to the conductive filaments (CFs). With further annealing, substitutional Cu becomes predominant via In sites. After annealing, supersaturated Cu forms nonuniform, crystalline CuInO clusters in a‐IGZO, which decrease the electrical conductivity of a‐IGZO and deteriorate the CF‐based RS performance. The findings reveal Cu diffusion mechanisms and the role of Cu in the electrical properties of AOSs dependent on the structural location and provide guidelines for modulating the RS characteristics of AOSs through Cu diffusion control. Abstract : The effects of dynamic copper diffusion on the electrical properties of amorphous oxide semiconductors (AOSs) are investigated. As the dominant copper diffusion site is altered from the free volume to the substitutional sites as a function of the annealing conditions, the electrical conductivity and the resistive switching characteristics of AOSs are dynamically altered.